CHRONIC BRONCHITIS IN EARLY SCHOOL AGE. - Mirzo Ulug‘bek Ulug‘bekov Oybek ugli (TADQIQOTLAR.UZ, 2024)
Annotation: Chronic bronchitis, a prolonged inflammation of the bronchi, is a common respiratory issue in early school-aged children. This article provides a comprehensive analysis of the causes, symptoms, and effects of chronic bronchitis in children, emphasizing the importance of early detection and appropriate management. The research aims to analyze the available literature on the topic, present findings from recent studies, and offer practical recommendations for both healthcare providers and parents.